0199 Effect Of Short-term Ambient Light Exposure On Subjective Sleepiness. (27th April 2018) - Mao, T; Yang, M; Yang, J; Luo, X; Ji, Y; Wang, Y; Zhou, G
Abstract: Introduction: Since the discovery of intrinsically photosensitive retinal ganglion cells, researchers found that light exerts powerful non-visual effects on numerous biological functions and behaviors in human, including circadian phase resetting, melatonin suppression, and enhancement of alertness. Of which, the alertness or sleepiness are most sensitive to short-wavelength light, and many studies focused on the effects of light exposure on sleepiness. However, few studies had investigated the effects of after short-term light exposure on sleepiness. Therefore, the study aimed to explore whether individual sleepiness would decrease after different short-term ambient light exposure in young adults. Methods: Eighty-seven healthy young adults (38 males, Mean age = 19.95 years, SD = 1.94 years) participated the 3 (ambient light) x 2 (order) within-subject design experiment. Three different ambient lights were red light (2.9 × 10 13 photons/cm 2 /s, 632nm, 110 lx), blue light (2.9 × 10 13 photons/cm 2 /s, 459 nm, 45 lx) and white light (110 lx) respectively. The Karolinska Sleepiness Scale (KSS) was used to assess subjective sleepiness. Participants completed KSS in white light first, then they were exposed to different ambient light to do same cognitive tasks for approximately 40 mins, and reported their subjective sleepiness again. Results: Repeated measure ANOVA indicated that neither significant main effect of ambient light ( p = .232) or interaction effect of ambient light and order ( p = .835) were found; while there was a significant main effect of order ( p < .001, η p 2 = 0.549) on subjective sleepiness, that is, participants' subjective sleepiness increased significantly after completing 40 mins cognitive tasks independent of ambient light. Conclusion: These results suggest that there was no non-visual effect appeared after 40 mins light exposure, for subjective sleepiness increased in all three ambient light. Thus, it seems that people should take a break after about 40 mins continuous work to relieve fatigue, whether in the white, red or blue light. Support (If Any): This work has been funded by the National Key Research and Development Program of China (No.2016YFB0404202) and the National Natural Science Foundation of China (Grant No. U1501244, 51561135014).